Representations of finite p-groups over the ring of formal power-mode series with integral p-addic coefficients - Gudivok , P. M.; Oros , V. M.; Roiter , A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A classification is given of the representations of the cyclic group of order p over the ring ℤp[[х]]  of formal power series with integral p-adic coefficients and it is proved that in the other cases the problem of representations of a finite, p-group over ℤp [[х1, ..., xn]] is wild.